An analysis of two indigenous reproductive health illnesses in a Nahua community in Veracruz, Mexico - Smith-Oka Vania (BMC, 2012)
Abstract Background This article describes the local concepts indigenous Nahua women hold regarding their reproduction. Specifically it provides a description of two indigenous illnesses-isihuayo and necaxantle, it discusses their etiology, symptoms, and treatments, and it analyzes them within the local ethnomedical framework and sociopolitical context. A perception of female vulnerability is shown to be an underlying shaper of women's experiences of these illnesses. Methods This research took place in a small Nahua village in Mexico. Qualitative data on local perceptions of these illnesses were collected by a combination of participant observation and interviews. Ethnobotanical data was obtained through interviews, and medicinal plants were collected in home gardens, fields, stream banks, and forested areas. The total study population consisted of traditional birth attendants (N = 5), clinicians (N = 8), and laywomen (N = 48). Results Results showed that 20% of the village women had suffered from one or both of these illnesses. The article includes a detailed description of the etiology, symptoms, and treatments of these illnesses. Data shows that they were caused by mechanical, physical, and social factors related to a woman's weakness and/or lack of support. Traditional birth attendants often treated women's illnesses. Five medicinal plants were salient in the treatment of these illnesses: Ocimum basilicum L., Mentzelia aspera L., Pedilanthus tithymaloides (L.) Poit., and Piper umbellatum L. were used for isihuayo, while Solanum wendlandii Hook f. was used for necaxantle. Conclusions The research on these two ethnomedical conditions is a useful case study to understanding how indigenous women experience reproductive health. Reproductive health is not simply about clinically-based medicine but is also about how biomedicine intersects with the local bodily concepts. By describing and analyzing indigenous women's ill health, one can focus upon the combination of causes-which extend beyond the physical body and into the larger structure that the women exist in.